Leadership Styles And Organizational Justice In The Public Health Sector Of Hawassa City (Ethiopia) - Alemu, Yared; Seth, Navneet (Journal of Neonatal Surgery, 2025)
This study investigated the influence of leadership styles on organizational justice perceptions among 516 employees across public hospitals in Hawassa City, Ethiopia. Using an explanatory research design with multi-stage random sampling, data were collected through validated questionnaires adapted from the Multifactor Leadership Questionnaire and Organizational Justice Scale. While the study achieved excellent instrument reliability (Cronbach's α = 0.97). Multiple linear regression results revealed significant relationships between all three leadership styles and organizational justice, with transformational leadership emerging as a strong positive predictor (B = .302, p < .001), it is characterized by its focus on cultivating a shared vision, inspiring followers, and demonstrating individualized consideration, demonstrates notable efficacy in cultivating perceptions of workplace fairness. Similarly, transactional leadership demonstrated an even stronger association (B = .351, p < .001), it contributes favorably to employees' perceptions of justice. Conversely, laissez-faire leadership exhibited significant negative prediction (B = -.266, p < .001), laissez-faire leadership's passive and avoidant traits weaken employees' sense of organizational justice. The results align with social exchange theory, demonstrating how active leadership behaviors foster reciprocal fairness perceptions, while passive styles erode them. For healthcare administrators, these findings suggest that: 1) structured transactional approaches may provide immediate justice benefits in high-pressure clinical settings, 2) transformational leadership offers complementary long-term cultural benefits, and 3) passive leadership requires urgent remediation.